Influence of Carbon Contact Strip Wear Profile on the Dynamic Performance of Pantograph-Catenary System - WANG Xuyang; ZHOU Ning; ZHI Xingshuai; LI Zhiwei; ZHANG Weihua; LU Xiaobing; YANG Jia; YANG Yihong (Chengshi guidao jiaotong yanjiu)
［Objective］ The carbon contact strip abnormal wear profile will reduce the dynamic coupling performance of the pantograph-catenary (PC), deteriorate the current collection quality, and accelerate the wear of the carbon contact strip and the contact wire. In order to find out the key carbon contact strip wear parameters that deteriorate the PC dynamic contact performance, it is necessary to study the influence of the carbon contact strip wear profile on the PC dynamic performance. ［Method］ A rigid flexible hybrid dynamic model of the pantograph considering the carbon contact strip wear profile is established, to study the influence of different carbon contact strip wear profiles on the PC dynamic performance. The accuracy of the model is verified by the measured data of the subway line. On this basis, the carbon contact strip wear profile is modeled through the measured wear profile data of the carbon contact strip after wear, and the contact force response under different profiles is studied. ［Result & Conclusion］ The fundamental frequency of the span passing frequency and the multiple frequency of the pantograph vertical movement make a greater contribution to the not-in-service profile, and each frequency band has influence on the contact force for the profiles in service; when the height difference of carbon contact strip is less than 1.5 mm, the standard deviation and maximum value of the contact force increase rapidly; when the height difference of carbon contact strip is 1.5~3.0 mm, the standard deviation and maximum value of the contact force remain in relatively stable state; when the height difference of carbon contact strip exceeds 3.0 mm, the standard deviation and maximum value of the contact force increase rapidly, with the maximum value exceeding 300 N.